Microtekties in sediments from the Brunhes-Matuyama transition - Schneider, David A; Kent, Dennis V; Mello, Gilberto A (Supplement to: Schneider, DA et al. (1992): A detailed chronology of the Australasian impact event, the Brunhes-Matuyama geomagnetic polarity reversal, and global climate change. Earth and Planetary Science Letters, 111(2-4), 395-405, https://doi.org/10.1016/0012-821X(92)90192-X, 1992)
A mechanism had been recently proposed to show how an impact event can trigger a geomagnetic polarity reversal by means of rapid climate cooling. We test the proposed mechanism by examining the record from two high sedimentation rate (8-11 cm/kyr) deep-sea sediment cores (ODP Sites 767 and 769) from marginal seas of the Indonesian archipelago, which record the Australasian impact with well-defined microtektite layers, the Brunhes-Matuyama polarity reversal with strong and stable remanent magnetizations, and global climate with oxygen isotope variations in planktonic foraminifera. Both ODP cores show the impact to have preceded the reversal of magnetic field directions by about 12 kyr. Both records indicate that the field intensity was increasing near the time of impact and that it continued to increase for about 4 kyr afterwards. Furthermore, the oxygen isotope record available from sediments at ODP Site 769 shows no indication of discernible climate cooling following the impact: the microtektite event occurred in the later part of glacial Stage 20 and was followed by a smooth warming trend to interglacial Stage 19. Thus the detailed chronology does not support the previously proposed model which would predict that a decrease in geomagnetic field intensity resulted from a minor glaciation following the impact event. We conclude that the evidence for a causal link between impacts and geomagnetic reversals remains insufficient to demonstrate a physical connection.